Evaluation of dystrophic calcification in juvenile dermatomyositis and systemic sclerosis - Marimar Saez-de Ocariz (Instituto Nacional de Pediatría, 2014)
Background: Dystrophic calcification is associated with juvenile dermatomyositis and progressive systemic sclerosis. The clinical diagnosis is established with detection of subcutaneous and petrous nodules. Conventional x-ray methods may evidence calcium deposits; however, in the case of incipient deposits x-ray may be insufficient. There are studies that use Tc99-MPD labeled bone scintigraphy to identify dystrophic calcification. Objectives: Estimate the frequency of dystrophic calcification in patients with juvenile dermatomyositis and progressive systemic sclerosis and CREST syndrome, and the concordance between the diagnosis of dystrophic calcification obtained by physical exploration and that obtained by scintigraphy. Patients and methods: A comparative, observational, and transverse study conducted in patients of one and the another gender, between 5 and 17 years of age, with diagnosis of juvenile dermatomyositis, progressive systemic sclerosis, and CREST syndrome to detect dystrophic calcification by physical exploration and scintigraphy. Fisher's exact test was performed to evaluate the association between the two diagnostic methods, and the Kappa test was used for the level of concordance and analysis of distribution by group and extent of dystrophic calcification. The sensitivity and specificity of scintigraphy in detecting dystrophic calcification in soft tissues, bony protrusions, costal arches and vertebrae were also estimated. Results: The overall incidence of calcinosis was 80%. In 16 patients dystrophic calcification was detected by dermatological physical exploration and in 9 patients by scintigraphy. No association or concordance was found between the findings from physical exploration and scintigraphic findings. The latter have 37.5% sensitivity for detection of dystrophic calcification in soft tissues and 43.8% in bony protrusions, and are suitable for detection in costal arches. Conclusions: Dermatological exploration and scintigraphy are complementary tools for detecting dystrophic calcification.